Low-density clustering effects of Skyrme interactions in nuclear matter - Aguilera, V. C.; Andrade, S. G.; Zimerman, A. H.; Döhnert, L.; De Llano, M.; Plastino, A. (My University, 1977)
An orthonormal set of single-nucleon orbital functions, explicity satisfying the Hartree-Fock equations for occupied states, is introduced and shown to display, assuming several parameterizations of the Skyrme interaction, α-clustering effects at low densities in nuclear matter. NUCLEAR MATTER Hartree-Fock; nuclear structure. © 1977 The American Physical Society.